1966
DOI: 10.1029/jz071i014p03427
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear decoupling, full and partial

Abstract: An underground explosion in a cavity is said to be fully decoupled if the cavity is large enough for the explosion to produce only elastic motion in the walls; in a smaller cavity where the wall motion is elastoplastic, the explosion is said to be partially decoupled. In this report, the pressure histories on the walls of cavities in salt of suitable size for decoupling sources are calculated and used in computing the motions of the walls, including the effect of elastoplastic behavior of salt. From the motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Reduction of the device yield would reduce the initial concentrations of radioactivity correspondingly. Costs quoted in Table V-b are based on [9,12,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduction of the device yield would reduce the initial concentrations of radioactivity correspondingly. Costs quoted in Table V-b are based on [9,12,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Copper extraction coefficients were 10 or higher in all tests. Ruthenium-106, the most troublesome radiocontaminant in the cementation process, had extraction coefficients of less than 0.005 over this pH range, as did 134 Cs, 85 Sr, 6°C o, 46 Sc, 6 Zn, and 144 Ce. Further study of the extraction of 95 Zr-Nb, 5 Fe, and 110 Ag showed extractions of the first two to be time dependent (Fig.…”
Section: Of Eleven Radionuclides Tested Onlymentioning
confidence: 99%
See 3 more Smart Citations